2015
DOI: 10.4103/0970-4388.160407
|View full text |Cite
|
Sign up to set email alerts
|

Management of congenital choanal atresia: A pedodontist′s role

Abstract: Choanal atresia is a rare cryptic congenital anomaly with developmental failure of the nasal cavity to communicate with the nasophaynx, resulting in a significant physiological and anatomical alteration of the dento-facial complex. It is considered as a life-threatening or lethal congenital malformation in an obligatory nasal breathing neonate. Elective transnasal endoscopic repair is the most preferred and minimally invasive procedure to correct this anomaly. This case report describes the multi-disciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In two step reactions, hydrazinolysis of substituted methyl benzoates gave acid hydrazides 7 which, on addition to CS 2 , sodium monochloroacetate (8) and hydrazine hydrate afforded benzamidothiosemicarbazides (N-aroyl thiocarbohydrazides (9a-c (Scheme 7) [14].…”
Section: From Acid Hydrazidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In two step reactions, hydrazinolysis of substituted methyl benzoates gave acid hydrazides 7 which, on addition to CS 2 , sodium monochloroacetate (8) and hydrazine hydrate afforded benzamidothiosemicarbazides (N-aroyl thiocarbohydrazides (9a-c (Scheme 7) [14].…”
Section: From Acid Hydrazidesmentioning
confidence: 99%
“…It was reported that a mixture of 3- dene)amino]thiourea derivatives 15a-j (43-56%) and N 0 ,2bis(2-oxoindolin-3-ylidene)-hydrazine-1-carbothiohydrazine (16) (20-31%), was effectively obtained by the reaction between (substituted-ylidene) thiocarbonohydrazides 13a-j with isatin malononitrile (14) with stirring at r.t in absolute ethanol and few drops of piperidine (Scheme 9) [16].…”
Section: Reaction With 134-oxadiazole-2-thionementioning
confidence: 99%
See 1 more Smart Citation